Implementation of Social Forestry for Community Welfare (Case study: Social Forestry in Bandung Regency) - Fachri, Mohammad; Nurliah Nurdin; Khasan Effendy; Ika Sartika (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The massive tourism and plantation industries have increased the rate of deforestation in the forest areas of Bandung Regency. This study aims to analyze the implementation of Social Forestry in Bandung Regency. The research employs a descriptive qualitative approach. Bandung Regency is used as a case study location for the implementation of social forestry. Data collection activities were conducted from March to June 2024. The implementation of social forestry is hindered by the lack of support for Forest Farmer Groups. The issue of insufficient communication of the program by the local government is marked by the minimal outreach to forest groups and the community. Findings on the implementation of social forestry programs indicate that the programs have not yet reached their target.